The First World War : a very short introduction - Howard, Michael, 1922-2019 (Very short introductions, 2007)
By the time the First World War ended in 1918, eight million people had died in what had been perhaps the most apocalyptic episode the world had known. This book provides a concise history of 'the Great War', focusing on why it happened, how it was fought, and why it had the consequences it did.